HLA-G, -E and -F regulatory and coding region variability and haplotypes in the Beninese Toffin population sample. (December 2018) - Sonon, Paulin; Sadissou, Ibrahim; Tokplonou, Léonidas; M'po, Kuumaaté K.G.; Glitho, Sonya S.C.; Agniwo, Privat; Ibikounlé, Moudachirou; Massaro, Juliana Doblas; Massougbodji, Achille; Moreau, Philippe; Sabbagh, Audrey; Mendes-Junior, Celso T.; et al.
Highlights: HLA-G/E/F are the most conserved HLA class I genes even in Africans. Despite population diversity selection pressures maintained low HLA-E/F/G diversity. Conserved protein diversity supports the immunomodulatory role of HLA-E/F/G. Toffin ethnic group could be considered as a rich repository for genetic variation. Abstract: HLA-G/E/F genes exhibit immunomodulatory properties and are expressed in placenta. Little attention has been devoted to the study of these genes in sub-Saharan African populations, which are yet the most diverse. To fill this gap, we evaluated the complete gene variability, approximately 5.1 kb for HLA-G (n = 149), 7.7 kb for HLA-E (n = 150) and 6.2 kb for HLA-F (n = 152) in the remote Beninese Toffin population, using massive parallel sequencing. Overall, 96, 37 and 68 variable sites were detected along the entire HLA-G, -E and -F, respectively, arranged into region-specific haplotypes; i.e., promoter haplotypes (16, 19, and 15 respectively), coding haplotypes (19, 15, and 29 respectively), 3' untranslated region (3′UTR) haplotypes (12, 7 and 2, respectively) and extended haplotypes (33, 31 and 32 respectively). All promoter/coding/3'UTR haplotypes followed the patterns already described in worldwide populations. HLA-E was the most conserved, exhibiting mainly two full-length encoded-molecules (E*01:01 and E*01:03), followed by HLA-F, three full-length proteins (F*01:01, F*01:02 and F*01:03) and HLA-G, four proteins: three full-length (G*01:01, G*01:03 and G*01:04) and one truncated (G*01:05N). Although HLA-G/E/F alleles in the Toffin population were the most frequently observed worldwide, the frequencies of the coding haplotypes were closely similar to those described for other African populations (Guinea-Conakry and Burkina-Faso), when compared to non-African ones (Brazilian), indicating that variable sites along these genes were present in Africa before human dispersion.